PENGARUH PENGENDALIAN INTERN PIUTANG TERHADAP MINIMALISASI PIUTANG TAK TERTAGIH PADA PT. AL IJARAH TAHUN 2014 - Effendi, Syahril (MEASUREMENT : Jurnal Program Studi Akuntansi, 2015)
The main activity of the leasing company is financing the procurement of goods, the customer will be paid by installment. Every customer is given the long time limit penyicilannya depending on the agreement with the customer's company. Operating systems such company is certainly not immediately generate cash receipts, but the cause of trade and then later on the day of maturity ocurs cash inflows.Accounts receivable at thecompany is generallythe largest partofcurrent assetsas well asthe largestpartofthe totalassets ofthe company. Therefore,control oftrade receivablesisveryimportantditerapkan.Gunareduceandminimizebad debts.Â Key words:Internal Control, Bad Debt